Hereditary Dental Diseases – Clinical Diagnosis and Strategies for Treatment and Rehabilitation - Sologova, Susanna Sergeevna; Rzaeva, Aidan Elchin kizi; Tereshkina, Olga Ivanovna; Sologova, Diana Igorevna; Vlasova, Natalia Nikolaevna; Arazashvili, Liana Davidovna (Open Access Macedonian Journal of Medical Sciences, 2020)
AIM: The research has been aimed at optimization of approaches to diagnosis, prevention, and treatment strategies to the hereditary dental diseases based on the analysis of modern relevant information. METHODS: Using the methods of content analysis and cluster analysis, the information included in periodicals, as well as educational and non-regulatory publications for the period of 2011–2019, was systematized and structured; the analysis of sources devoted to modern approaches to the diagnosis, prevention, and treatment of hereditary dental diseases, their genetic etiology, with the description of clinical cases and illustrations for each example, was conducted; hereditary dental diseases were classified; based on a comparative analysis, approaches to the diagnosis, treatment, and prevention of these diseases were optimized. RESULTS: The most significant hereditary dental diseases have been identified, the classification of approaches to their diagnosis and treatment has been presented, the scheme of drug therapy has been optimized depending on the pathology. CONCLUSION: The systematic analysis of information on hereditary dental diseases with the description of clinical cases for each nosology has been carried out for the 1st time, and the approaches to their diagnosis and treatment have been optimized with due consideration of domestic and foreign experience.